Why Female Smokers Have Poorer Long-Term Health Outcomes than Male Smokers: The Role of Cigarette Smoking During Pregnancy - Li Yang; Li Yang; Yunchun Zhou; Yunchun Zhou; Mingyan Jiang; Wendy Wen; Yanfang Guo; Yanfang Guo; Smita Pakhale; Smita Pakhale; Smita Pakhale; Shi Wu Wen; et al. (Frontiers Media S.A., 2024)
Objectives: Women's health status is better than men but the opposite is true for female smokers who usually have poorer long-health outcomes than male smokers. The objectives of this study were to thoroughly reviewed and analyzed relevant literature and to propose a hypothesis that may explain this paradox phenomenon.Methods: We conducted a search of literature from three English databases (EMBASE, MEDLINE, and Google Scholar) from inception to 13 November 2023. A combination of key words and/or subject headings in English was applied, including relevant terms for cigarette smoking, sex/gender, pregnancy, and health indicators. We then performed analysis of the searched literature.Results: Based on this review/analysis of literature, we proposed a hypothesis that may explain this paradox phenomenon: female smokers have worse long-term health outcomes than male smokers because some of them smoke during pregnancy, and the adverse effects of cigarette smoking during pregnancy is much stronger than cigarette smoking during non-pregnancy periods.Conclusion: Approval of our pregnancy-amplification theory could provide additional evidence on the adverse effect on women's long-term health outcomes for cigarette smoking during pregnancy.